Microcephaly, mental retardation, cataracts, and hypogonadism in sibs: Martsolf's syndrome. - Harbord, M G (1989)
The association of microcephaly, mental retardation, cataracts, and hypogonadism is described in sibs (brother and sister) of consanguineous parents. These features are consistent with a diagnosis of Martsolf's syndrome. In addition, one sib had a cardiomyopathy while the other had cardiac failure.